A negação da educação étnico-racial nas escolas estaduais e municipais da cidade de São Paulo - Silva, Andrew Souza (2018)
In this research, we intend to analyze comparatively educational proposals regarding Ethnic-Racial relations in the teaching of Afro-Brazilian and African History and culture offered by the state and municipal public education in the city of São Paulo. Racism, historically present and widespread in the various layers of Brazilian society, is nowadays a major problem to be overcome. In fact, racist practices that have historically been present in the daily social relations of the country is also part of the school context. Accordingly, the school environment, which is thought by all as beneficial, where part of the students' identity is build, can also depreciate and stigmatize them. Therefore, this research contributes to identifying and searching for alternatives in order to solve the problem of growing racism in educational institutions, which stems from the lack of the making of a quality education that values the historical diversity of the black population